Developing Contextual Textbooks of Islamic Religious Education on Curriculum Development and Innovation Course - Khasanah, Uswatun (Al-Hayat: Journal of Islamic Education, 2024)
This research aimed to develop a textbook for the PAI (Islamic Education) Curriculum Development and Innovation course as a means of independent student learning. This is development research referring to the ADDIE (Analyze, Design, Develop, Implement, Evaluate) development model. The subjects of this research were Islamic education Masters students at the Mamba'ul 'Ulum Islamic Institute (IIM) of Surakarta. The data were collected using textbook assessment instruments consisting of (1) tryout instruments by course content experts, (2) tryout instruments by learning design experts, (3) practitioner instruments, and (4) student assessment instruments. The data were analyzed using qualitative and quantitative descriptive methods. The research results showed that a score percentage of 89% was obtained for the expert assessment of course content, a score of 75% for the learning design expert assessment tryout, a score of 90% for the practitioner tryout results, and a score of 87.75% for the student assessment tryout. Based on the research results, it could be concluded that the textbook for the Islamic education curriculum development and innovation course belonged to the appropriate category and could be used for students taking the Islamic education curriculum development and innovation course at the IIM Surakarta Postgraduate School, especially Masters students in Islamic education.